Upaya Peningkatan kualitas Pelayanan Posyandu Balita Berbasis Informasi di Desa Maguwan Kecamatan Sambit Kabupaten Ponorogo - Chotimah, Chusnul (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The existence of Intergrated service post in the community aims to improve public health,especieally toddlers.one of the activities at Intrgrated service posts is to weigh and record the development of children every month and then recover data to be reported to the Regional Health Office.many intregated service posts which do data recording still using manual way that data wrintten in book administration Post service intergrated which cause data less accurate,relevant and efficient. Including intergrated service post in maguwan village sambit district ponorogo regence which is the location of comunity service activity. The methods used in the design of information systems are observation, interview,requarement analysis, syistem desing and syistem implementation. The result of comunity service is the availability of intergated service post information syistem that can improve proccessing data administration of intergrated post syistematicaliy, effectively, and efficiently and facilitate the chadres in monitoring the development of todler and facilitate in preparing reports in accordance with the standards of the regional health of fice.this web-based information syistem also supports responsive display, which not only can be accessed in personal computar (PC) but also in tabblet and smarphone.